'The role of youth organizations in peacebuilding in the African Great Lakes Region: a rough transition from local and non-governmental to the national and governmental peacebuilding efforts in Burundi and eastern DRC'. Issue 2 (3rd May 2020) - Kasherwa, Amani C.
ABSTRACT: The youth is generally considered as the pillar of society. However, over the last many years, the views, power and potentials of the youth in the Great Lakes Region (GLR) have not been effectively harnessed in peacebuilding initiatives. Despite their ever-increasing numbers and influence at community level; young people are frequently overlooked in programmes for the prevention, response and transformation of conflicts. In extremely difficult conditions, some youth organizations are constructively contributing to promoting the culture of peace at community level. However, initiatives of these youth organizations are limited by the prevailing resistance to the emerging youth culture, inadequate institutional support, financial constraints and the failing post-war transition to peace. Based on a broader empirical study on the role of youth organizations in peacebuilding in the GLR; this article critically examines the lack of a smooth transition for young people from efforts at the local and non-governmental level to the national and governmental level in Burundi and DRC. It also describes a diversity of conceptualizations of 'peace' shaping the different approaches of youth organizations for peace. The article also examines the challenges affecting youth constructive participation in peacebuilding and suggests some reflections for effectively harnessing youth's power and potential for building sustainable peace and reconciliation in the region.